Training development of meat-based BASECHI to improve the quality of public health in meatball vendors - Rina Sugiarti Dwi Gita; Fauzan Adhim; Mochammad Mulana Tri Anggono; Linda Ike Septyaningsih (University of Merdeka Malang, 2024)
The large number of meatball producers who still use dangerous preservatives needs to be stopped. The use of alternative natural preservatives that do not cause side effects on consumers such as chitosan needs to be introduced so that it can be used by many people. BASECHI (Chitosan Healthy Meatballs) development training includes a series of socialization activities designed to empower meatball traders with the knowledge and skills in making meatballs containing chitosan, a natural compound that has important health benefits. The activity begins with participants undergoing a pre-test to measure initial knowledge. Providing material by experts on the benefits of chitosan and techniques for making healthy meatballs. Practicing chitosan application to meatballs and continuing with a post-test session to assess participants' knowledge. The program ends with closing activities that include discussion, feedback, and further planning to ensure the continuity and sustainability of the knowledge gained. The expected results of this training are increased awareness of traders about the importance of food quality, mastering skills in making healthy meatballs, and improving the quality of public health through the consumption of more nutritious products.